Carbohydrate Chemistry [Vol.41] - Pilar, Amelia Rauter [Ed.]; K Lindhorst,Thisbe [Ed.]; Queneau, Yves [Ed.] (UK: RSC, 2016)
With the increase in volume, velocity and variety of information, researchers can find it difficult to keep up to date with the literature in the field. As the synthesis of novel carbohydrates and carbohydrate mimetics continues to be a major challenge for organic chemists, not least because of the increasingly interdisciplinary nature of carbohydrate science, Carbohydrate Chemistry Volume 41 will prove invaluable. Covering both chemical and biological science, this series collates modern carbohydrate research from theory to application and will be of great benefit to any researcher who wishes to learn about the latest developments in the carbohydrate field.
Keywords: Organic Chemistry -- Carbohydrates